“BRASH Therapy” on Quality of Life Among Nursing Home Residents: A Pre-Experimental Study - Ni Luh Putu Dian Yunita Sari; I Kadek Prastikanala; Ni Wayan Yunnita Ceatra Jayathi; Pande Putu Riskyana; Meity Coryaningsih; Nabilla Rosa Nada Febriana; Ni Putu Ayu Gangga Restu Wedayanti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Elderly residing in nursing homes are susceptible to health issues, which can significantly impact their quality of life. This study aims to evaluate the effect of “BRASH Therapy” (Benson Relaxation, Affirmation, Butterfly Hug, and Self-Healing Touch Therapy) on the quality of life of the elderly. Methods: A quantitative approach employing a pre-experimental pre and post-test design was utilized in this study. The sample consisted of 65 participants selected through purposive sampling technique. The inclusion criteria are able to communicate in Indonesian, able to stand, and had no injuries to the upper and lower extremities. Meanwhile, the exclusion criteria set were elderly people with mental and cognitive disorders, as well as chronic mobility disorders. The intervention provided was “BRASH Therapy” administered over five sessions, each lasting fifteen minutes. The quality of life of the elderly was measured pre an post the completion of all intervention sessions. The instrument used for this measurement was the WHOQOL-BRIEF, which has been validated and is reliable. Due to the data not being normally distributed, the Wilcoxon test was used for processing. This research has been declared ethically receivable with evidence of passing ethical review with Ethical Approval Number 283/EA/KEPK-BUB-2024. Results: The majority of the respondents in this study were female (78,5%), with an average age of 74,3 years. The findings revealed median quality-of-life scores increased from 48,5 (IQR = 20,25-76,75) at baseline to 70,5 (IQR =20,25-80,50) post-intervention. The bivariate test indicated a statistically significant result (Z = ?6,758, p < 0,001). The calculated effect size was very large (r = 0,84, 95% CI: 0,74–0,90), indicating substantial practical significance. Thus, participation in “BRASH Therapy” showed statistically significant improvement of quality of life among elderly residing in nursing homes. Conclusion: The findings can serve as a basis for considerating complementary interventions aimed at improving the quality of life of elderly residing in nursing homes.